The Beale ciphers in fiction. Issue 4 (4th July 2019) - Dooley, John F.
Abstract: The Beale ciphers are an interesting unsolved cryptographic puzzle, if for no other reason than their solution may uncover the location of a multimillion-dollar treasure. That is, if they are not a hoax. Over the years many cryptanalysts, amateur and professional, have tried and failed to decrypt the final two Beale ciphers. Recently, a number of writers have used the ciphers in their works of fiction. I review ten such novels and a short animated movie that all use the Beale ciphers as plot elements. The novels fall into two categories. First are novels where the objective is to solve the Beale ciphers and find the treasure. These novels use probable and improbable techniques to find the solutions. In some the solution occurs out of sight so the reader has no insight into the cryptanalysis. Second are novels where the existence of the Beale ciphers and their construction as book ciphers further a different story narrative. In these novels the Beale ciphers are mentioned and described but no attempt is made to solve them. There is usually another book cipher that must be solved instead. In conclusion, the Beale ciphers still seem to be generating significant interest.